Oral health status among the adult tobacco users in a selected rural area of Bangladesh (Update Dental College Journal, 2018)
Tobacco use is a primary cause of many oral diseases and adverse oral conditions and it is a risk factor for oral cancer, periodontal diseases, congenital defects such as cleft lip and palate in children whose mother smokes during pregnancy. A cross sectional study was conducted among 190 adult tobacco users in Charpaterdoho Union, Madarganj Upazilla, Jamalpur District, during the period from July 2013 to December 2013 to assess the oral health status of the adult tobacco users in rural area of Bangladesh. Data were collectedby using pre tested interview administered questionnaire andto assess the oral health status intra oral examination was performed by a dental surgeon assisted by two trained and calibrated investigators. Both descriptive and inferential statistics has been used for analysis of data with the help of Statistical Package for Social Science SPSS (Version 21) software on the basis of different variables. The study result revealed that out of 190 respondents maximum 61 (32.1%) belongs to 18-28 years age group, majority 116 (61.1) % were male. Among the respondents tobacco used in different ways like cigarette, ‘Gul’, ‘Zorda’, betel leaf, ‘Sadapata’ consumption where cigarette was the commonly used form of tobacco and the least commonly used form of tobacco was betel leaf and ‘Sadapata’. In intra oral examination this study result revealed that around 50 (26%) respondents dentition condition was healthy, and 121 (63.7%) respondents had less than 25% decayed teeth, 115(60.5%) respondents had periodontitis, around less than three fourth 132 (69.5%)had gingivitis,almost all (95.3%) had dental deposition or plaque and 155 (81.6%) respond- ents had no functional prosthesis. In logistic regression analysis monthly family income level (p =.004) was significantly associated with oral health status when the adjusted with other variables (education, sex, age). Sex and age were not associated with oral health status. Exposure to tobacco is a signifi- cant, modifiable risk factor for different oral diseases, so the changing attitude can be occurred by giving adequate information and motivation to the mass people along with dental health education.Update Dent. Coll. j: 2017; 7 (2): 04-08